Women's Empowerment in YA Fantasy - Kuntová, Kateřina (Univerzita Pardubice, 2025)
This thesis analyzes the empowering nature of women in contemporary young adult high fantasy novels. The theoretical part defines the genre and introduces different points of view on the topic as well as offering its own definition. Furthermore, it deals with women's role in the world in the terms of showing their emotions as a reaction to injustice, stereotypes, as well as the representation of queer people. The larger part of the paper deals with four novels and analyzes aspects of these novels that are used to empower the main characters. First, it focuses on secondary worlds and the circumstances heroines deal with. In the last section, characters themselves are described along with their powers, qualities, imperfections and empowering nature.
Keywords: young adult fantasy; feminismus; vysoká fantasy; reprezentace; young adult fantasy; feminism; high fantasy; representation